Significance of depression in family caregivers of critically ill patients discharged home - Oh, Eui Geum; Lee, Hyun Joo; Yang, You Lee; Kim, oung Man (Journal of Thoracic Disease, 2016)
Readiness for discharge is an important factor that influences negative health outcomes such as unplanned readmission, aggravation of caregiver stress and increases healthcare costs (1). In particular, caregivers of critically ill patients have higher burdens in patient care because of lack of professional knowledge on patient conditions, social supports and community resources (2-5).